The influences of training on rowers of different age - Lasan, M.; Katic, R. (Collegium Antropologicum, 2000)
We measured 14 rowers and divided them into two groups according to age and years of training. Our goal has been to establish the influence of several years of programmed training on the structure of the body, oxygen carrying capacity and oxidation capacity of muscle cells, the chemical composition of blood and characteristics of pulse and lactate curves in rowers. As to the structure of the body, the two groups did not differ if we equalised them according to body height. Differences existed in the determinants of oxygen carrying capacity and oxidation capacity of muscle cells. Older rowers had lower pulse at rest, higher step test index, lower pulse immediately after the step test and in the last minute of the test on a bicycle ergometer and higher maximal oxygen pulse. While at rest, no significant differences between the groups were observed in most of the analysed substances in the blood serum. With the increase of age and training period an increase of the concentration of creatinin and activity of creatine kinase and lessening of the activity of alkaline phosphatase was noted. Length of training period lowers the levels of cholesterol and free fatty acids and increases the level of triglycerides in blood serum. An increase of the activity of creatine kinase and lactate dehydrogenase and the formation of a specific pattern of isoenzymes was observed. The pulse and lactate curve flattened and moved to the right.